Uji Performance Alat Uji Pengereman Kereta Cepat Untuk Kecepatan 160 km/jam - Bakhri, Mohammad Samsul; Rusnaldy, Rusnaldy; Paryanto, Paryanto (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2024)
Indonesia is currently developing an international standard high-speed train industry. One of the important components of the fast train is the braking system. The fast train braking test rig at Diponegoro University has a speed of 160 km/h using a pneumatic braking system accompanied by disk brake and brake pad components for high speed. The performance test of the fast train braking test equipment needs to be done to find out if the test rig is in accordance with PT INKA standards and ensure it is safe to test. The purpose of this research is to test the performance of the braking test equipment, including the deceleration, braking distance, and mechanical vibration criteria. Measurement of deceleration and braking distance is carried out using a tachometer sensor and stopwatch, while mechanical vibration is measured using a vibration meter. The test results of deceleration and braking distance obtained were then compared with PT INKA standards, and the results of vibration signals obtained were then compared with ISO 10816 vibration level standards. The results showed that in normal braking conditions with a pressure of 3.8 bar, the average value of deceleration was 1.44 m/s2 , and the braking distance was 684 m. In emergency braking conditions with a pressure of 5 bar, the average value of deceleration was 2.70 m/s2 , and the braking distance was 365 m. The resulting mechanical vibration shows on bearing 1 the average Vrms value on the horizontal accelerometer of 0.03 in/s, the vertical accelerometer of 0.01 in/s, and the axial accelerometer of 0.01 in/s, and on bearing 2 the average Vrms value on the horizontal accelerometer of 0.02 in/s, the vertical accelerometer of 0.01 in/s, and the axial accelerometer of 0.01 in/s. From these vibration results, it can be concluded that the vibration conditions in accordance with ISO 10816 are safe to operate.